Proposed Amendments to the Special Data Dissemination Standard Plus and the Annex on the General Data Dissemination System. (Policy Papers; Policy Paper ;, 2015)
The Special Data Dissemination Standard Plus (SDDS Plus) was established in October 2012 to reinforce and supplement the Fund's Data Standards Initiatives and assist Fund members who decide to adhere to the SDDS Plus with regard to the publication of comprehensive, timely, accessible, and reliable economic and financial statistical data in a world of continuing economic and financial integration. The SDDS Plus also requires adherents to disseminate metadata to promote public knowledge and understanding of their compilation practices with respect to the required data categories. During the Ninth Review of the Fund's data Standards Initiatives in May 2015 executive directors supported changing the transition period to meet all SDDS Plus requirements to five years after the adherence date. On July 1, 2015, the Executive Board approved the proposed change. The existing rules governing the SDDS Plus are superseded by the new SDDS Plus legal text.